Power generation provider and power consumer bidding method and device based on multi-type markets - CHEN YUGUO; ZHOU WANPENG; YANG LIBIN; MENG XINYU; YANG YING; WANG XIANQIANG; HU HONGJU; SHI ANQI; LI CHUNLAI; WANG MAOCHUN; WANG LIANFANG; CAO CHUNLIAN (2021)
The invention relates to a power generation provider and power consumer bidding method and device based on multi-type markets. The method comprises the following steps: constructing a power generation provider multi-market bidding strategy model and a user multi-market bidding strategy model; and combining the generator multi-market bidding strategy model, the user multi-market bidding strategy model and the power market bilateral bidding clearing model to determine the bidding of the market members. According to the invention, a multi-type market-based power supplier and power consumer bidding model considering the carbon market, the green certificate market and the power market is designed, joint modeling of the carbon market, the green certificate market and the power market is realized, and market types and market behaviors participated by different market subjects are fully considered, the multi-type member quotation decision problem under the multi-market coexistence condition is solved, and the maximum